Corporate Approach in Work-Integrated Learning for Students of Engineering Programs - Karstina, S.G.; Tussupbekova, A.K. (International Journal of Learning, Teaching and Educational Research, 2025)
The intensifying integration of engineering, science, and education, along with the growing requirements for graduates’ professional competencies, underscores the need for innovative and systematically structured approaches to engineering education. One such approach is the corporate model, which involves coordinated actions of all educational stakeholders and the integration of students into real industrial environments. This study proposes an adapted model of work-integrated learning based on a corporate approach, implemented in the engineering programs of a university in Kazakhstan. Unlike many models described in the literature, the emphasis is placed not only on industrial practice but also on comprehensive resource and organizational coordination between universities and companies. The model incorporates principles of institutional partnership, joint program design and assessment, and is supported by empirical analysis of company attractiveness factors, interaction formats, and the evaluation of four workplace dimensions. The pilot implementation of the model demonstrated an improvement in students’ skills ranging from 5.46% to 16.74%. A total of 91.67% of students positively assessed the organization of workplace learning, and 83.33% highlighted the overall attractiveness of the model. The effectiveness of the model was confirmed using t-tests and one-way analysis of variance (ANOVA). The findings suggest that this model can be recommended for implementation in engineering programs of universities in developing countries.
Keywords: bachelor's degree program; corporate approach; engineering education; work-integrated learning; project work